When foreign waves hit home shores: Organizational identification in psychological contract breach–violation relationships during international assignments - Tassilo Schuster; Benjamin Bader; Anna Katharina Bader; Denise M. Rousseau (Journal of Organizational Behavior, 2021)
In the context of international assignments, this study investigates the psychological contract breach–violation relationship from a multiparty employment perspective. Multiparty employment refers to arrangements where employees have concurrent psychological contracts with more than one party. Drawing on two waves of survey data from 221 expatriates, we find both direct relationships and asymmetric spillover effects of psychological contract breach on violation. Psychological contract breach by either the home or host organization is directly linked to psychological contract violation by the breaching party. Additionally, spillover effects occur such that a breach by the host predicts psychological contract violation by the home organization, though not the reverse. These relationships are shaped by the expatriates' organizational identification. Identification with the host buffers the direct effect between breach and violation by the host, while dual organizational identification mitigates the direct effect between breach and violation by the home organization. Identification with the home organization diminishes the spillover effect from host breach to home organization violation. The opposite, identification with the host, amplifies the spillover effect of host breach to home organization violation. By examining the distinct dynamics of home and host organization contract breach and violation, we develop theoretical implications for understanding PCs in multiparty work arrangements.
Keywords: 650; expatriates; multiparty perspective; organizational identification; psychological contract